WASp Deficiency Selectively Affects the TCR Diversity of Different Memory T Cell Subsets in WAS Chimeric Mice - Li, Wenyan; Jia, Yanjun; Wang, Yanping; Zhao, Qin; Yang, Lu; Zeng, Ting; Niu, Linlin; Dai, Rongxin; Li, Yanan; Zhao, Xiaodong; Wu, Junfeng (Frontiers in Immunology, 2022)
Background The T cell receptor (TCR) diversity is essential for effective T cell immunity. Previous studies showed that TCR diversity in Wiskott–Aldrich Syndrome (WAS) patients was severely impaired, especially in the memory T cell populations. Whether this defect was caused by intrinsic WASp deficiency or extrinsic reasons is still unclear. Methods We sorted different T cell subsets from the bone marrow chimeric mice model using both magnetic beads and flow cytometry. TCR repertoires of memory T cells, especially CD4+ effector memory T (TEM) cells and CD8+ central memory T (TCM) cells, were analyzed using the UMI quantitative high-throughput sequencing (HTS). Results An average of 5.51 million sequencing reads of 32 samples was obtained from the Illumina sequencing platform. Bioinformatic analyses showed that compared with wild type (WT), WAS knock out (KO)-CD4+ TEM cells exhibited increased Simpson index and decreased D50 index (P <0.05); The rank abundance curve of KO-CD4+ TEM cells was shorter and steeper than that of WT, and the angle of qD and q in KO-CD4+ TEM cells was lower than that of WT, while these indexes showed few changes between WT and KO chimeric mice in the CD8+TCM population. Therefore, it indicated that the restriction on the TCRVβ repertoires is majorly in KO-CD4+ TEM cells but not KO- CD8+ TCM cells. Principal Component Analysis (PCA), a comprehensive parameter for TCRVβ diversity, successfully segregated CD4+ TEM cells from WT and KO, but failed in CD8+ TCM cells. Among the total sequences of TRB, the usage of TRBV12.2, TRBV30, TRBV31, TRBV4, TRBD1, TRBD2, TRBJ1.1, and TRBJ1.4 showed a significant difference between WT-CD4+ TEM cells and KO-CD4+ TEM cells (P <0.05), while in CD8+ TCM cells, only the usage of TRBV12.2 and TRBV20 showed a substantial difference between WT and KO (P <0.05). No significant differences in the hydrophobicity and sequence length of TCRVβ were found between the WT and KO groups. Conclusion WASp deficiency selectively affected the TCR diversity of different memory T cell subsets, and it had more impact on the TCRVβ diversity of CD4+ TEM cells than CD8+ TCM cells. Moreover, the limitation of TCRVβ diversity of CD4+ TEM cells and CD8+ TCM cells in WAS was not severe but intrinsic.